Apolipoprotein E Gene Polymorphisms in Essential Hypertension: A Preliminary Study with Meta-analysis - Wisam, NI; Norsidah, KZ; Samsul, D; Zamzila, A; Rafidah, HM; Norlelawati, AT (Int Islamic Univ Malaysia, Kulliyyah Medicine, 2024)
Indexed by WOS/ Scopus